INCREASING AWARENESS AND READERSHIP OF TRIBUN JAWA TENGAH NEWSPAPER AS COMMUNICATION MANAGER - Windariani Soeryo Handadari; Djoko Setyabudi, S.Sos, MM (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Tribun Jawa Tengah is a brand of newspaper which is a subsidiary of Kompas Gramedia Group. Established on January 17, 2011, Tribun Jateng has a early name Warta Jawa Tengah, and then turns into Tribun Jawa Tengah on 29 April 2013. Tribun Jawa Tengah has a vision to be the group's largest regional media publishing business, spread and leading in Central Java with the slogan